Disaster Loses in the Developing World: Evidence from the August 1999 Earthquake in Turkey - Bradley T. Ewing; Jamie B. Kruse; Özlem Özdemir (Turkish Economic Association, 2004)
The purpose of this study is to investigate the impacts of a natural disaster on a developing countrys economy. In that sense, we look at the impact of August 1999 earthquake in Turkey on two important macroeconomic indicators of the Turkish economy (Real Output and Employment) with recovery policies followed by the government and international donors. Our results indicate that the earthquake had a significant immediate negative impact on both output and employment growth in Turkey. While output growth reverted back to its predisaster pattern after the initial shock, employment growth did not recover. The earthquake had both a short run and long run influence on the Turkish economy. This study will develop understanding of the possible effects of future earthquakes. Also, it will help the Turkish Government evaluate already-applied mitigation measures (like Turkish Catastrophe Insurance Pool etc.) and guide the preparation for forthcoming disasters since scientists have reached a consensus that a major earthquake is expected in Istanbul.
Keywords: 330